Security and Justice Overview : Security and Justice Thematic Paper - Harborne, Bernard; Sage, Caroline (World Bank, Washington, DC, 2017)
The central theme of the 2011 World Development Report (WDR) is that violent conflict remains a constant threat to human rights, peace and sustainable development. While the nature of violent conflict maybe changing1 its negative impact on poor people in terms of rights violations, public health, forced displacement and diminution of life chances is the same. Critical to establishing peace and the necessary confidence between state and citizen is providing a sense of security, freedom from fear, and the protection of basic rights and entitlements. The purpose of this paper is to analyze the relationship, overlapping and sometimes contradictory, between a range of approaches to security and justice in conflict affected contexts, and to place these efforts within a broader rule of law framework. This, it will be argued, greatly assists in addressing the kind of frictions and blind-spots that commonly exist in making the transition from violence to peace. The paper will then examine some of the instruments and approaches adopted by governments and international partners in addressing the kinds of stresses which result in violent conflict. Finally, it will examine the gaps in the international arena which continue to persist in this area of support. A series of security and justice-themed papers produced for the WDR 2011 outline in more detail the issues, approaches and lessons of the key components including: security, public security in peacekeeping settings, criminal justice, justice and administrative law, and transitional justice.